Fully resolved measurements of turbulent boundary layer flows up to $Re_{\unicode[STIX]{x1D70F}}=20\, 000$. (20th July 2018) - Samie, M.; Marusic, I.; Hutchins, N.; Fu, M. K.; Fan, Y.; Hultmark, M.; Smits, A. J.
Abstract : Fully resolved measurements of turbulent boundary layers are reported for the Reynolds number range $Re_{\unicode[STIX]{x1D70F}}=6000{-}20\, 000$ . Despite several decades of research in wall-bounded turbulence there is still controversy over the behaviour of streamwise turbulence intensities near the wall, especially at high Reynolds numbers. Much of it stems from the uncertainty in measurement due to finite spatial resolution. Conventional hot-wire anemometry is limited for high Reynolds number measurements due to limited spatial resolution issues that cause attenuation in the streamwise turbulence intensity profile near the wall. To address this issue we use the nano-scale thermal anemometry probe (NSTAP), developed at Princeton University to conduct velocity measurements in the high Reynolds number boundary layer facility at the University of Melbourne. The NSTAP has a sensing length almost one order of magnitude smaller than conventional hot-wires. This enables us to acquire fully resolved velocity measurements of turbulent boundary layers up to $Re_{\unicode[STIX]{x1D70F}}=20\, 000$ . Results show that in the near-wall region, the viscous-scaled streamwise turbulence intensity grows with $Re_{\unicode[STIX]{x1D70F}}$ in the Reynolds number range of the experiments. A second outer peak in the streamwise turbulence intensity is also shown to emerge at the highest Reynolds numbers. Moreover, the energy spectra in the near-wall region show excellent inner scaling over the small to moderate wavelength range, followed by a large-scale influence that increases with Reynolds number. Outer scaling in the outer region is found to collapse the energy spectra over high wavelengths across various Reynolds numbers.